The Relationship Between Knowledge, Attitudes, and Motivation of Pregnant Women in Practicing Prenatal Yoga at Wiradesa Health Center - Sandi Ari Susiatmi; Sifanis Azzahra (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2026)
The study titled "The Relationship Between Knowledge, Attitudes, and Motivation of Pregnant Women in Practicing Prenatal Yoga at Wiradesa Health Center" aims to explore how knowledge relates to attitudes and motivation in pregnant women regarding prenatal yoga. It used random sampling with 100 pregnant women who practiced prenatal yoga for 6 months. The data were analyzed using both descriptive and inferential statistics. Findings reveal that most pregnant women have a solid understanding and positive attitudes towards prenatal yoga. Additionally, there is a significant link between knowledge and motivation, with most women showing both good knowledge and high motivation. The study concludes that a pregnant woman’s knowledge about prenatal yoga impacts her attitudes and motivation to practice it.